The Quest for an Antibody-Based HIV Vaccine - Haynes, Barton F. (Immunol Rev, 2017)
Despite major advances in our understanding of the biology of HIV-1 infection, and advances in antiretroviral therapy to treat the disease, there were 2.1 million new cases of HIV-1 infection in 2015, and 36.7 million people living with AIDS (http://www.unaids.org/en/resources/fact-sheet). Thus, a vaccine that can prevent HIV-infection remains a global priority. Thirty-three years after the discovery of HIV-1(1), and the demonstration it was the cause of AIDS(2) and after 6 HIV-1 vaccine efficacy trials (3–8), no HIV-1 candidate vaccine has shown enough efficacy to be approved for clinical use. Of several vaccine concepts tested in efficacy trials, only one, the RV144 pox virus prime, protein boost (ALVAC/AIDSVAX B/E) vaccine, showed a low level of vaccine protection with an estimated 31% vaccine efficacy (8). Candidate vaccines have sought to elicit both antibody and T-cell responses, but to fully prevent the acquisition of infection, a major focus has been on the induction of protective antibody responses (9, 10). Hence, the focus of this issue of Immunologic Reviews is “Antibodies and Immunity to HIV”. Animal models have demonstrated that passive administration of HIV-1-- neutralizing antibodies can fully protect against infection, but the induction of such antibodies via immunization remains a major scientific challenge. With recent advances in the isolation and characterization of broadly neutralizing antibodies (bnAbs) from HIV-1-infected subjects, in elucidating structures of the HIV-1 envelope glycoprotein (Env), in defining novel approaches to immunogen design, and in improved understanding of the immunological pathways leading to bNAb elicitation, the challenge developing an HIV-1 vaccine appears to be more tractable. The articles in this issue highlight both major areas of HIV-1 vaccine development progress and remaining obstacles, and provide context for the renewed optimism that a highly effective vaccine, while not imminent, is possible.